Effect of nutrients enriched feed premix on the growth performance of major carps Rohu, Catla and Mrigal in a polyculture system - Rahman, Md Faridur; Sultana, Shamima; Kabiraj, Manash; Alimullah, Md (Asian Journal of Medical and Biological Research, 2018)
To evaluate the effect of nutrients enriched feed premix on the growth performance of major carps Rohu (Labeo rohita), Catla (Catla catla) and Mrigal (Cirrhinus mrigala) in a polyculture system, the present experiment was carried out in six earthen ponds located at Khulna University of Bangladesh for a period of 90 days. Two treatments each with three replications were stocked with 40% Rohu, 30% Catla and 30% Mrigal with a total stocking density of 10000/ha. T-2 was treated with feed premix at the rate of 4g/1 kg feed while T-1 was not treated with any feed premix. Both treatments were applied normal feed twice a day at the rate of 2% to 4% of the body weight of the fingerlings. The net fish production was found to be 2238.06 kg/ha and 3607.33 kg/ha in T-1 and T-2 respectively. The results showed that fish production was significantly higher in T-2 than T-1 (P<0.05). T-2 showed 0.60 times greater fish production than that of T-1. Asian J. Med. Biol. Res. September 2018, 4(3): 298-306